What they know vs. what they do: How acquirers leverage technology acquisitions - Puranam, Phanish (Institutional Knowledge at Singapore Management University, 2007)
Existing research suggests that in acquisitions of small technology-based firms by large established firms post-merger integration both enables and hinders acquirers' efforts to leverage the technology of acquired firms. This apparent paradox can be resolved once we account for the qualitatively distinct ways in which acquirers leverage technology acquisitions. Integration helps acquirers use the acquired firm's existing knowledge as an input to their own innovation processes (leveraging what they know), but hinders their reliance on the acquired firm as an independent source of ongoing innovation (leveraging what they do). We also show that experienced acquirers are better able to mitigate the disruptive consequences of the loss of autonomy entailed by integration, though we find no evidence that they achieve greater coordination benefits from integration.